Bi‐level planning model for optimal allocation of WT–PV–ESS in distribution networks. Issue 13 (19th December 2017) - Liu, Yuan; Yang, Jun; Zhu, Xu; Wang, Yang; He, Bo; Zhu, Jie; Chen, Yanxia
Abstract : Study on how renewable power generation (RPG) can be used efficiently and effectively in distribution networks is open and ongoing. Here, a bi‐level model is proposed to optimise the allocation of photovoltaic (PV), wind turbine (WT), and energy storage system (ESS) in distribution networks. At the upper level, genetic algorithm (GA) is used to optimise the capacity of PV and WT in each bus by minimising the cost of investment and maintenance (I&M), power purchase, and power losses, considering the constraints of the RPG penetration limit, power flow equation, voltage limits, and feeder capacity limits. At the lower level, an operation strategy of ESS is proposed first to smooth the power flow. Based on this operation strategy of ESS, the capacity estimation of ESS is completed with regard to the load power data. Then an optimisation model designed by exhaustive search is utilised for sitting the ESS in distribution network, with objectives of minimising the cost of I&M and power electronics in ESS. The proposed bi‐level model for optimal allocation of WT–PV–ESS is verified under a 33‐node test feeder. Also, the numerical results show that the proposed bi‐level model enables a power utility to identify the optimal location and size of PV–WT–ESS for a clear reduction on power purchase and power losses after the PV and WT's access and a benefit on load shaving after the connection of ESS.